The Effect of Dangke on Changes in Total Cholesterol and Triglyceride Levels in Obesity White Rats - A.Sahra Salsabilla; Asrini Safitri; Rezky Pratiwi L.Basri; Aryanti Bamahry R; Dian Fahmi Utami (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Background: Obesity is the excessive accumulation of fat in the body which disrupts health with the risk of metabolic system disorders in the form of increased cholesterol and triglycerides in the blood. The prevalence of obesity in Makassar City is 24.05%, which is the highest prevalence in South Sulawesi. Dangke contains Lactic Acid Bacteria in the form of probiotics which have the ability to anti-inflammatory mechanisms and fat metabolism in the body. Purpose: To determine the effect of dangke on changes in total cholesterol and triglyceride levels in obese white rats. Method: Pure experimental research design with Pre Post Randomized Clinical Trial Design. Data analysis used the independent T test/Mann-Whitney test and paired T test/Wilcoxon Signed Rank Test with a value of <0.05. Results: Comparison of total cholesterol and triglyceride levels before and after intervention in the control group showed p-values of 0.12 and 0.01, meaning there was no significant change in cholesterol and there was a significant change in triglycerides. Comparison of total cholesterol and triglyceride levels before and after intervention in the dangke group p-values were 0.47 and 0.12, meaning there was no significant change in total cholesterol and triglyceride levels. The difference in total cholesterol and triglyceride levels before the intervention in the control and dangke groups showed p-values of 0.37 and 0.78, meaning there was no significant change in total cholesterol and triglyceride levels. The difference in total cholesterol and triglyceride levels after intervention in the control and dangke groups obtained p-values of 0.38 and 0.32, which means there was no significant change in total cholesterol and triglyceride levels. Conclusion: There was no significant change in total cholesterol and triglyceride levels in the control and dangke groups when given dangke, but there was a tendency to decrease total cholesterol and triglyceride levels after the intervention in the dangke group.